2020
DOI: 10.1029/2019jg005534
|View full text |Cite
|
Sign up to set email alerts
|

Outgoing Near‐Infrared Radiation From Vegetation Scales With Canopy Photosynthesis Across a Spectrum of Function, Structure, Physiological Capacity, and Weather

Abstract: We test the relationship between canopy photosynthesis and reflected near‐infrared radiation from vegetation across a range of functional (photosynthetic pathway and capacity) and structural conditions (leaf area index, fraction of green and dead leaves, canopy height, reproductive stage, and leaf angle inclination), weather conditions, and years using a network of field sites from across central California. We based our analysis on direct measurements of canopy photosynthesis, with eddy covariance, and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 92 publications
3
70
0
Order By: Relevance
“…The annual grassland also experienced a wide range in the duration of its physiologically active period. The day of year that the grassland became senescent ranged between day of year 129 and 172 (Baldocchi et al., 2020). We examined the correlation between the sums of annual evapotranspiration with the day of year photosynthesis ceased and found it explained only 15% of its inter‐annual variation.…”
Section: Resultsmentioning
confidence: 99%
“…The annual grassland also experienced a wide range in the duration of its physiologically active period. The day of year that the grassland became senescent ranged between day of year 129 and 172 (Baldocchi et al., 2020). We examined the correlation between the sums of annual evapotranspiration with the day of year photosynthesis ceased and found it explained only 15% of its inter‐annual variation.…”
Section: Resultsmentioning
confidence: 99%
“…Differences between NIRVP and NIRV regarding their correlation to SIF and GPP are expected to become more important when using data from upcoming geostationary satellite missions such as GeoCarb, TEMPO and Sentinel-4 2 . As canopy-level PAR cannot be directly observed from airplanes or satellites, either a simple approach that approximates PAR via the downwelling NIR radiance 22,37,40 , or more complex methods involving atmospheric radiative transfer modelling 38,55 or machine learning 56 can be used. The radiance-based approach has previously been shown to have comparable performance with direct PAR observations at the site level 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Since one of the major goals of SIF research is to improve remote sensing based GPP estimation 1,7 , it is important to also compare the performance of SIF and NIRVP for this purpose. Several recent studies demonstrated the promise of using NIRV and NIRVP to estimate GPP across multiple spatial scales 33,[37][38][39] .…”
mentioning
confidence: 99%
“…When interpreting spaceborne SIF observations, it is important to consider that SIF likely mirrors changes in carbon assimilation as a function of APAR chl and to a lesser degree tracking photosynthesis at the physiological level for most ecosystems. This is particularly true for crops, or annual species, where changes in APAR chl often mirror GPP (Baldocchi et al, 2020; Dechant et al, 2020); however, in structurally invariant evergreen forests with little to no understory, a seasonal increase in sustained NPQ will reduce ΦF, permitting the tracking of photosynthetic downregulation with SIF (Magney, Bowling, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%